Augmented Reality gamified experience for Phage biology science communication - Chloe James (6251534) (2025)
This project is a gamified augmented reality (AR) application prototype designed to make phage biology accessible and engaging through science communication. Developed through collaboration between microbiology researchers, creative technologists, and developers from the University of Salford, the University of Liverpool, and FeedAR, a company specialising in web-based AR experiences. The prototype offers a user experience tailored for science exhibitions, providing visitors with an interactive way to learn about phages and their role in controlling bacterial outbreaks. Using AR, players can interact with three-dimensional phage models, selecting them from a scientifically informed collection or designing their own through a stamping and colouring process. These custom creations are digitised and transformed into 3D models using generative AI. All phages, whether curated or user-generated, are stored in an online database accessible through a “microscope view,” where the entire collection can be explored. Within the AR interface, these models become in-game pieces that players launch to combat virtual bacterial outbreaks. This first prototype was showcased at the British Science Festival 2025 in Liverpool on September 13, offering a playful yet scientifically grounded introduction to the world of phage biology.